Development of a depot formulation with an in situ non-lamellar liquid crystal-forming system with phospholipids - Hiroaki Todo; Rina Niki; Akie Okada; Ibuki Narita; Kazuya Inamura; Ayu Ito; Shoko Itakura; Ichiro Hijikuro; Kenji Sugibayashi; Kenji Sugibayashi (Frontiers in Drug Delivery, 2023)
Non-lamellar liquid crystal (NLLC) structures have gained increasing attention for the controlled release of entrapped drugs. In the present study, an in situ NLLC structure-forming depot formulation through contact with water was developed using a ternary mixture system of soya phosphatidyl choline (SPC), 1, 2-dioleoyl-sn-glycero-3-phosphoglycerol sodium salt (DOPG), and sorbitan trioleate (Span 85), and the long-term release of an entrapped model drug, leuprolide acetate (LA), was investigated using evaluation of in vitro release and in vivo blood concentration–time profiles. Polarized images and small angle X-ray scattering analysis were used to confirm the presence of NLLC structures by contacting the prepared formulation with water. In addition, LA release and blood concentration–time profiles were investigated using in vitro and in vivo experiments, respectively. In situ NLLC constructed formulations by contacting water were achieved using a ternary mixture of SPC, DOPG, and Span 85. In particular, negative curvature was increased with an increase in the amount of Span 85 in the formulation, and an Fd3m structure was obtained with a sustained release of LA. A maintained blood concentration of LA over 21 days was confirmed by subcutaneous (s.c.) administration of the formulation. No retained administered formulation at the injection site was confirmed 28 days after administration without any signs of irritation, inflammation, or other apparent toxicity confirmed by visual observation. This result may be helpful for the development of a lipid-based formulation of peptides and proteins with sustained drug release.